2021
DOI: 10.1007/s00170-021-06772-6
|View full text |Cite
|
Sign up to set email alerts
|

Real-time monitoring and control for high-efficiency autonomous laser fabrication of silicon nanoparticle colloids

Abstract: Nanotechnology is a significant research tool for biological and medical research with major advancements achieved from nanoparticle (Np) applications in biosensing and biotherapeutics. For laser ablation synthesis in solution (LASiS) to be chosen by researchers for Np colloid production, the process must effectively compete with chemical synthesis in terms of produced colloid quality and productivity while taking advantage of LASiS benefits in terms of its 'green-synthesis' and single-step functionalisation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…2) to confirm nanoparticle formation. The absorption peaks in the 400 nm wavelength region confirm silver nanoparticle formation under the experimental conditions: pulse repletion rate, fPRF = 20 kHz, process duration, t=30 min, and laser bean scan speed, v =2.2 mm s -1 in DI water [39]. The inset of Fig.…”
Section: Resultsmentioning
confidence: 64%
“…2) to confirm nanoparticle formation. The absorption peaks in the 400 nm wavelength region confirm silver nanoparticle formation under the experimental conditions: pulse repletion rate, fPRF = 20 kHz, process duration, t=30 min, and laser bean scan speed, v =2.2 mm s -1 in DI water [39]. The inset of Fig.…”
Section: Resultsmentioning
confidence: 64%
“…From Figure 2 d, it can also be observed that no secondary peaks were observed for all the nanoparticles produced USP and by LASiS operated under batch and recirculation mode. The absence of secondary peaks shows the stability of AgNPs in the solution [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…For batch LASiS, the target material was placed in a beaker and submerged in 4 mL of DI water. For recirculatory flow LASiS, an in-house designed polymer 3D-printed flow cell described, previously described in the literature contained the target material [ 19 , 20 , 21 ]. A peristaltic pump (Millipore Ltd., Burlington, VT, USA) was used to maintain a recirculating flow of DI-water over the AG target surface at 100 mL min −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1987, Patil et al first explored material synthesis at a solidliquid interface using a pulsed laser (ruby laser with a pulse width of 30 ns) by generating metastable iron oxide from an iron substrate in water [23]. Later in 1993, Neddersen et al reported the generation of organic solvent and water based stable colloids, without any ionic or organic species, from metal targets such as Cu, Pt, Pd, Au and Ag via laser ablation [24]. The LASiS technique has been used for the generation of highly pure nanostructures in aqueous solutions at room temperature and normal pressure conditions since 2000 [14,[25][26][27][28] and several NP colloids of metals (e.g., Ag [29], Cu [29,30] and Au [31]), polymers [32], semiconductors (e.g., silicon carbide (SiC) [33], silicon (Si) [34] and zinc oxide (ZnO) [35]) and carbon (C) [36] have been synthesized using this method.…”
Section: Introductionmentioning
confidence: 99%